The mediating role of students’ satisfaction towards perceived performance during COVID-19 Open and Distance Learning (ODL) / Humairaa Hasan - Hasan, Humairaa (2022)
The Malaysian government has announced that the education system will change from a physical to an online environment due to the COVID-19 outbreak. This is the best educational option and case prevention. Even though the suggested move was an appropriate one based on the situation, it was still a very hasty decision since widely implementing a new educational environment in the educational community has caused pressure and challenges in an already stressful event. Although management, faculty, and students have all accepted the new educational norm after a few years, there are still challenges. This study explores the Higher Education Institutions (HEIs) situation, focusing on the Accounting Education community in conducting classes using the Open and Distance Learning (ODL) medium during COVID-19. Due to unpreparedness, the community has been facing difficulties in digitising its courses. It is an exploratory study that caters to accounting students' experiences during ODL and centres around Students’ Satisfaction as a mediator and Perceived Performance as the dependent variable, as well as indulging the factors that impact them.